Creating inclusive financial sectors to address SDGs: factors that influence access from an African context - Mugwabana, Tsimbe (Graduate School of Business (GSB), 2021)
In many developing economies, access to and subsequent utilisation of mainstream financial services act as a barrier to financial inclusion. The merging of financial services and information technology, especially by means of mobile devices, result in consumers being able to make use of financial services at any time and place, thereby overcoming the distribution challenges and subsequent use (Gu, Lee, & Suh, 2009). This research examined the factors influencing the continued use of tech-based financial services post adoption by the Base of the Pyramid (BOP) in South Africa. The research uses the risk-benefit framework to understand usage behaviour focusing on cost, convenience, perceived ease of use and risk (security and operational) as predictor variables. The research makes use of analysed secondary data on 481 low-income individuals using the Structural equation modelling (SEM).The partial least squares structural modelling was utilised to test the hypotheses and relationship between the variables. The findings indicate that perceived benefit has a greater influence on usage than perceived risk. Even though consumers consider both benefit and risk in decision making, the expectation of potential benefits is a greater driver of usage. Convenience, cost and perceived ease of use were found to have significant impacts on usage, with the latter two having the greatest impacts. Perceived risk had a significant but weak impact on usage, with operating risk influencing usage more than security risk. The research recommends that when creating a value proposition for Fintech products, resources should be weighted more towards improving and highlighting those factors that drive the perception of benefit or value added to customers (cheaper, quicker etc.) vs. those that manage a potential risk. Customers are likely to respond positively and increase usage when there is an additional benefit to be derived.